PM: S&T important to ummah - Abd Razak, Dzulkifli (2003)
THE writer was privileged to listen to the speech of the Prime Minister at the opening of the 10th Session of the Organisation of the Islamic Conference Summit in Putrajaya. On that day, the place, the event and the man seemed to converge on one vital element: the importance of science and technology (S&T), with specific reference to Muslims. Putrajaya is a madeinMalaysia example of how S&T can be put to good use as epitomised by the architecture and wetland and gardenlike environment. The summit, on the other hand, is about what happens if S&T is not given its meaningful place in development. The man, Datuk Seri Dr Mahathir Mohammad, is an ardent advocate of S&T.